The Influence Of Persuasive E-Wom Review In Social Media Toward Saudis Travel Intention - Alrasheedi, Najah Mohammed Khilaf (2022)
This study investigates the influence of the antecedents of persuasive eWOM reviews on tourists’ attitudes towards the destination abroad and the travel intention of Saudi tourists. The research also investigates the influence of trust as a moderate between antecedents of persuasive eWOM review and information acceptance.